Factors influence financial performance of the Takaful industry in Malaysia - Masnurah, Zain (2017)
Takaful is an Islamic insurance based on Sharia compliance. Takaful industry is an industry that contributes to the development of Malaysia. Thus the stability of the financial performance of the takaful industry is very important. This study is carried out due to the unstable financial performance of the takaful industry in Malaysia. The main objective of this study was to determine the relationship between leverage, size, equity capital and liquidity with the financial performance. This study is a quantitative research and data used are secondary data taken from the audited financial statement. This study is made up of all takaful operators in Malaysia for a period of five years from 2011 to 2015. When the study was conducted, a total of 11 takaful operators were registered with Bank Negara Malaysia (BNM). The financial performance is measured by Return on Assets (ROA). Leverage and liquidity was measured by ratio analysis whilst the size and equity capital was measured using a natural logarithm. To obtain the results of the study, the Statistical Package for the Social Sciences (SPSS) was used which consisted of descriptive statistics, normality test and multiple regressions analysis. The result of normality test was presented using histogram and p-p plot. The study found leverage and liquidity was not significant to the financial performance. Size have a significant and positive relationship with financial performance and equity capital have a significant but negative relationship with financial performance. The implications of this study can guide investors in making their investment decisions, customers in selecting favorable takaful policies and government in developing the takaful industry in Malaysia.